2012
DOI: 10.1097/nrl.0b013e3182675479
|View full text |Cite
|
Sign up to set email alerts
|

Monosymptomatic Clinically Isolated Syndrome With Sudden Sensorineural Hearing Loss

Abstract: This report describes a case of SSNHL in the context of magnetic resonance imaging of the brain and electrophysiological findings consistent with a demyelinating etiology. SSNHL is a rare and possibly underrecognized manifestation of clinically isolated syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
1
8
0
2
Order By: Relevance
“…62 Multiple sclerosis has been reported to present with SSNHL. 63,64 However, there are usually other focal neurologic symptoms or signs present simultaneously or previously. Isolated cranial nerve involvement is rare in patients with multiple sclerosis (10.4%), and isolated eighth nerve palsy is extremely rare (\1%).…”
Section: Supporting Textmentioning
confidence: 99%
See 1 more Smart Citation
“…62 Multiple sclerosis has been reported to present with SSNHL. 63,64 However, there are usually other focal neurologic symptoms or signs present simultaneously or previously. Isolated cranial nerve involvement is rare in patients with multiple sclerosis (10.4%), and isolated eighth nerve palsy is extremely rare (\1%).…”
Section: Supporting Textmentioning
confidence: 99%
“…Multiple sclerosis has been reported to present with SSNHL 63,64 . However, there are usually other focal neurologic symptoms or signs present simultaneously or previously.…”
Section: Key Action Statementsmentioning
confidence: 99%
“…While a population-based study suggests a relatively higher risk of SSNHL in MS among various autoimmune diseases [16], SSNHL is not commonly considered a prevalent symptom of MS [17,18]. Fortunately, the prognosis appears more favorable than idiopathic SSNHL, with most case reports of SSNHL in MS reporting hearing recovery [19][20][21][22][23][24][25][26][27][28]. However, these reports mainly involve unilateral SSNHL, and there is a lack of documented cases of bilateral SSNHL in MS.…”
Section: Introductionmentioning
confidence: 99%
“…Commonly diagnosed in clinical practice, SSNHL is one of the neurological and otolaryngological emergencies. So far, several studies have found that the pathogenesis of SSNHL may be associated with multiple diseases, such as Meniere’s disease, acoustic schwannoma, intracranial demyelination,1 7 8 and haemorrhagic or ischaemic stroke 1 9 10…”
Section: Introductionmentioning
confidence: 99%